2018
DOI: 10.1177/1591019918779229
|View full text |Cite
|
Sign up to set email alerts
|

Entry remnants in flow-diverted aneurysms: Does branch geometry influence aneurysm closure?

Abstract: Objective Numerous studies have suggested a relationship between delayed occlusion of intracranial aneurysms treated with the Pipeline Embolization Device (PED) and the presence of an incorporated branch. However, in some cases, flow diversion may still be the preferred treatment option. This study sought to determine whether geometric factors pertaining to relative size and angulation of branch vessel(s) can be measured in a reliable fashion and whether they are rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…23 It is also worth noting that many aneurysms arising from the distal vasculature are bifurcation aneurysms in some form and as such may well have a branch vessel incorporated into the aneurysm dome or neck. This configuration has previously been shown to slow the aneurysm occlusion rate 24,25 and for bifurcation aneurysms it has been said that a longer time frame for occlusion, perhaps upto 18 months, may be required for complete occlusion. 26,27 Similarly, with respect to Acom aneurysms the configuration may also play an important role in the success of flow diversion.…”
Section: Discussionmentioning
confidence: 99%
“…23 It is also worth noting that many aneurysms arising from the distal vasculature are bifurcation aneurysms in some form and as such may well have a branch vessel incorporated into the aneurysm dome or neck. This configuration has previously been shown to slow the aneurysm occlusion rate 24,25 and for bifurcation aneurysms it has been said that a longer time frame for occlusion, perhaps upto 18 months, may be required for complete occlusion. 26,27 Similarly, with respect to Acom aneurysms the configuration may also play an important role in the success of flow diversion.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 FD treatment failure is usually attributed to inadequate coverage of the aneurysm, presence of a pre-existing stent, presence of an incorporated branch, or endoleak analogous to that seen in endovascular abdominal aortic aneurysm repair. 47,48 However, these do not explain recurrence in completely occluded aneurysms. Other mechanisms that could explain recurrence are branch vessel runoff or improper endothelialization and thrombus formation leading to aneurysm recurrence and delayed rupture despite angiographic evidence of complete occlusion.…”
Section: Mechanism: Endothelializationmentioning
confidence: 99%
“…Some clinical trials have shown there is potential for recurrence of an aneurysm once it is completely occluded after treatment with an FD . FD treatment failure is usually attributed to inadequate coverage of the aneurysm, presence of a pre‐existing stent, presence of an incorporated branch, or endoleak analogous to that seen in endovascular abdominal aortic aneurysm repair . However, these do not explain recurrence in completely occluded aneurysms.…”
Section: Mechanism: Endothelializationmentioning
confidence: 99%